2018
DOI: 10.1210/jc.2017-02316
|View full text |Cite
|
Sign up to set email alerts
|

Proandrogenic and Antiandrogenic Progestins in Transgender Youth: Differential Effects on Body Composition and Bone Metabolism

Abstract: Proandrogenic and antiandrogenic progestins induce body composition changes in line with the desired appearance within 1 year of treatment. Bone health, especially at the lumbar spine, is of concern in trans girls, as bone mass accrual is severely affected by androgen suppressive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 40 publications
0
56
0
1
Order By: Relevance
“…Including Gooren and Bunck [62], 12 longitudinal studies [53,[63][64][65][66][67][68][69][70][71][72][73] have examined the effects of testosterone suppression on lean body mass or muscle size in transgender women. The collective evidence from these studies suggests that 12 months, which is the most commonly examined intervention period, of testosterone suppression to femaletypical reference levels results in a modest (approximately − 5%) loss of lean body mass or muscle size (Table 4).…”
Section: Muscle and Strength Metricsmentioning
confidence: 99%
“…Including Gooren and Bunck [62], 12 longitudinal studies [53,[63][64][65][66][67][68][69][70][71][72][73] have examined the effects of testosterone suppression on lean body mass or muscle size in transgender women. The collective evidence from these studies suggests that 12 months, which is the most commonly examined intervention period, of testosterone suppression to femaletypical reference levels results in a modest (approximately − 5%) loss of lean body mass or muscle size (Table 4).…”
Section: Muscle and Strength Metricsmentioning
confidence: 99%
“…During GnRHa treatment we observed a decline of aBMD and BMAD z-scores in line with previous studies ( 8-10 ). In transgirls a decrease of aBMD z-scores was also reported with the use of the anti-androgenic progestin cyproterone acetate ( 18 ). In contrast, 1 study showed that in transboys treated with the progestin lynestrenol for an average of 11.6 months aBMD z-scores were stable or increased ( 18 ).…”
Section: Discussionmentioning
confidence: 80%
“…In transgirls a decrease of aBMD z-scores was also reported with the use of the anti-androgenic progestin cyproterone acetate ( 18 ). In contrast, 1 study showed that in transboys treated with the progestin lynestrenol for an average of 11.6 months aBMD z-scores were stable or increased ( 18 ). If these results are confirmed, also with more prolonged treatment duration, the better safety profile with regard to bone health is an important point to discuss with adolescents.…”
Section: Discussionmentioning
confidence: 80%
“…87 Another recent study looked at the use of CPA in 21 late pubertal trans girls (Tanner 4 with mean bone age at study start of 17.1 ± 1.28 years) as a potential way to avoid the negative bone effects of GnRHas. 88 However, after 1 year of therapy there was a loss of lean mass and gain of fat mass as well as a decrease in Z -scores most profoundly at the LS, but also at the femoral neck and total hip. These findings all raise concerns, particularly since youth today are starting GnRHas earlier than in these studies (i.e.…”
Section: Part 2: Benefits Associated With Gahtmentioning
confidence: 91%